Session 5: How can I use EdTech to ensure that students are provided with quality educational content at the right level? - Mazari, Haani; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341509 ZenodoArchiveConcept: 7341508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341509 10.53832/edtechhub.0139 2405685:NUTI6KUS 2405685:PPRW2NTQ
Keywords: _r:AddedByZotZen

Telephone Survey: Caregivers' and Learners' Perspectives on SMS for Education in Kenya - Myers, Christina; Jordan, Katy; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia; Zhao, Annette (EdTech Hub, 2022)
This document presents the structure and questions used for a telephone survey which was undertaken with a sample of learners who use the M-Shule platform and their caregivers, in Kenya, during July and August 2022. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7310489 ZenodoArchiveConcept: 7310488 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7310489 10.53832/edtechhub.0133 2405685:NP52QFM8
Keywords: _r:AddedByZotZen

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6929534 10.53832/edtechhub.0123 2339240:7VEG4LSW 2405685:R4E96T5V 2405685:T9NZ63T3 2405685:VSHH2JUL
Keywords: _r:AddedByZotZen

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

EdTech Horizon Scan: Blockchain technology in education - Beoku-Betts, Iman; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking on a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This EdTech Horizon Scan examines the use of blockchain technology in education. Beginning with an overview of blockchain technology, the scan explains what blockchain technology is and how it works. The next section focuses on how blockchain technology can be used in education. In particular, it looks at the benefits of using blockchain technology for micro-credentialing and ownership of learning credentials, the transfer of credits and smart contracts, storing student credentials, identity verification and intellectual property protection. Section 4 gives a summary of the use of blockchain technology, noting the different challenges that may be associated with adopting blockchain technology into education systems. Section 5, gives real examples of the use of blockchain technology in education and different education institutions. Key words: blockchain; cryptography; data; decentralised database; digitalisation; education; micro-credentialing; smart contracting; student credentials; verification An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676491 10.5281/zenodo.6812384 10.53832/edtechhub.00101 10.53832/edtechhub.0101 2405685:94H68P58 2405685:S9XXPAHD 2405685:VJ84DKDF
Keywords: _r:AddedByZotZen

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
ZenodoArchiveID: 7139243 ZenodoArchiveConcept: 7139242 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7139243 10.53832/edtechhub.0122 2405685:Z8B66R9X
Keywords: _r:AddedByZotZen

Tackling coloniality in EdTech: Making your offering inclusive and socially just - Adam, Taskeen; Moustafa, Nariman; Sarwar, MoizzaBinat (EdTech Hub, 2022)
On 29 June 2022, Bertha Centre, EdTech Hub, Open Development & Education and the Overseas Development Institute (ODI) presented a workshop on Tackling Coloniality in EdTech. The workshop was hosted by Ntombini Marrengane (Bertha Institute). This slide deck shares the resources and activities used at the workshop, in the hope that it inspires others to host similar workshops that critically reflect on how coloniality can be embedded in EdTech designs, projects, programmes, processes, structures, values, knowledge systems, and philosophies.
ZenodoArchiveID: 7612943 ZenodoArchiveConcept: 7612942 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7612943 10.53832/edtechhub.0147 10.53832/edtechhub.0150 2405685:3QV8PAED
Keywords: _r:AddedByZotZen

Guidance on Facilitation of E-Learning - Dzinotyiweyi, Monica; Chuang, Rachel; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396251 10.53832/edtechhub.0087 2405685:CMEQA5F7
Keywords: F: Helpdesk response; _r:AddedByZotZen

School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6958056 10.53832/edtechhub.0106 2405685:MFH269TU
Keywords: _r:AddedByZotZen

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6339212 10.53832/edtechhub.0096 2339240:VJZWBP65 2405685:6JLQ7UC6 2405685:KQUDWCXC
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803101 10.53832/edtechhub.0077 2405685:VFV5SG9H
Keywords: _r:AddedByZotZen

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6337916 10.5281/zenodo.6337918 10.5281/zenodo.6338002 10.5281/zenodo.6338007 10.53832/edtechhub.0083 2339240:AZXVF44M 2339240:GZRZGRN7 2339240:MJPJVVCU 2405685:6QCZIQR2 2405685:D9VW8AI3 2405685:PWU63GQS 2405685:QAXG3NCJ 2405685:RKRPWPX5 2405685:VT5Z6XB6 2405685:YBG8MTTQ 2405685:ZDHGEBKD
Keywords: _r:AddedByZotZen

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

Key considerations when developing an ICT in Education strategy - AlSheikh Theeb, Thaer; Chuang, Rachel; Pandit, Sanjana (EdTech Hub, 2022)
This report was commissioned by UNICEF and produced under UNICEF and EdTech Hub’s global partnership, in response to a request from the UNICEF Laos team that was submitted to the EdTech Hub Helpdesk. It presents key considerations on the overarching process to develop an ICT in Education strategy (e.g., components, stakeholders, timelines) and lists examples of other national ICT in Education and EdTech strategies. Keywords: EdTech strategies; ICT in Education strategies An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6676586 10.53832/edtechhub.00100 10.53832/edtechhub.0100 2405685:2XS75XAU
Keywords: _r:AddedByZotZen

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6400980 10.53832/edtechhub.0086 10.53832/edtechhub.0088 2405685:29Z2JFJT 2405685:CB5GGAXU
Keywords: _r:AddedByZotZen

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5813529 10.53832/edtechhub.0084 2405685:DPWSAA9Z
Keywords: _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803107 10.53832/edtechhub.0076 2405685:CI5UZ5R4 2405685:HU5IFEK9
Keywords: _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803111 10.53832/edtechhub.0075 2339240:XBN27377 2405685:674LJ8EY 2405685:EW94QPAA
Keywords: _r:AddedByZotZen

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5032936 10.5281/zenodo.5142392 10.53832/edtechhub.0094 2405685:G9DHSZ57 2405685:HL6BNMQZ
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7336710 ZenodoArchiveConcept: 7336709 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7336710 10.53832/edtechhub.0136 2339240:4TCBX2GH 2405685:3QBCENK5 2405685:AWHK2L8L
Keywords: _r:AddedByZotZen

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245945 ZenodoArchiveConcept: 7245944 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245945 10.53832/edtechhub.0128 2405685:X8MUXS39
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396237 10.53832/edtechhub.0086 2405685:CVS2WZC3 2405685:FVSQD8MB
Keywords: F: Helpdesk response; _r:AddedByZotZen

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7003826 ZenodoArchiveConcept: 7003825 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7003826 10.53832/edtechhub.0118 2339240:3XB6YUXL 2405685:GXLAGDUM 2405685:RPR47JXT 2405685:ZXBB58KS
Keywords: _r:AddedByZotZen

الامتحانات عبر الإنترنت في سياقات الطوارئ: هل المراقبة، والتقنيات الأخرى، مجدية في سوريا لتيسير عقد امتحانات تشمل جميع الطلاب؟ - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; AlMekdad, Bayan; Sabboura, Rani; Sheqem, Yazeed (EdTech Hub, 2022)
كلمات مفتاحية: الامتحانات عبر الإنترنت، تكنولوجيا مراقبة الامتحانات، سياقات الطوارئ، سوريا خلاصة: الغرض من هذه الوثيقة تقديم دليل يمكن استخدامه من قبل الممارسين في مجال التعليم العاملين في سياقات الطوارئ لتقييم مدى جدوى تنفيذ الامتحانات الإلكترونية واستخدام تكنولوجيا مراقبة الامتحانات. سيتطلب عقد الامتحانات عالية المخاطر عبر الإنترنت في سوريا وفي سياقات طوارئ أخرى استثمارات كبيرة لتحقيق المتطلبات الأساسية اللازمة للجدوى والمصداقية. تشمل هذه المتطلبات الأساسية الكهرباء والإنترنت والأجهزة، بالإضافة إلى تطوير المهارات الرقمية اللازمة للطلاب لتقديم الامتحانات عبر الإنترنت وللمعلمين والإداريين لتيسير الامتحانات عبر الإنترنت. ينبغي بذل المزيد من الجهود لمنع تسريب المعلومات حول الأسئلة ومحتوى الامتحانات، ولتشجيع التغيير الثقافي حول الامتحانات عبر الإنترنت. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7143871 ZenodoArchiveConcept: 7143870 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7143871 10.53832/edtechhub.0124 2405685:9DZXFIC7
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6621244 10.53832/edtechhub.0098 2405685:GV4MKFZH
Keywords: _r:AddedByZotZen

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen